2003
DOI: 10.1109/tmag.2003.808990
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular recording near 100 Gb/in/sup 2/

Abstract: Theoretical analyses have projected perpendicular recording capable of achieving ultimate areal densities greater than longitudinal recording systems. For perpendicular recording to supplant longitudinal recording, laboratory demonstrations will need to be made which intercept or exceed the areal densities achieved by state-of-the-art longitudinal recording demonstrations. Recent demonstrations have come close to eliminating the gap between these technologies. In this paper, recording experiments at areal dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…the solid lines in figures 5(a) and 5(b) remain flat. (2) When the read width is W r = 40 nm = 2W/3, there is no conspicuous enhancement of track-edge noise in T1 if the guard-band width is larger than half of the track width, as seen in the dotted line in figure 5(a), which agrees well with previous experiments [6,16] and is similar to the PW 50 results for the longitudinal recording in [17]. (3) The total noise power of T1, with a read width W r = 60 nm, varies little with track pitch, as shown in the dashed line in figure 5(a).…”
Section: Dibit Noise Distributionsupporting
confidence: 90%
See 1 more Smart Citation
“…the solid lines in figures 5(a) and 5(b) remain flat. (2) When the read width is W r = 40 nm = 2W/3, there is no conspicuous enhancement of track-edge noise in T1 if the guard-band width is larger than half of the track width, as seen in the dotted line in figure 5(a), which agrees well with previous experiments [6,16] and is similar to the PW 50 results for the longitudinal recording in [17]. (3) The total noise power of T1, with a read width W r = 60 nm, varies little with track pitch, as shown in the dashed line in figure 5(a).…”
Section: Dibit Noise Distributionsupporting
confidence: 90%
“…Experimental studies have been carried out to investigate ATI in perpendicular recording [6][7][8]. Stray fields under different portions of the write head have been studied and a way of selecting an optimal write current has been proposed in [7].…”
Section: Introductionmentioning
confidence: 99%
“…Conceptual studies for areal densities of 1 Tbit/in have also been shown [2]- [5]. To achieve an areal density of 1 Tbit/in , it is necessary to reduce the side-writing field as well as obtain a large recording field strength with a narrow-track SPT heads as predicted in [6].…”
Section: Introductionmentioning
confidence: 99%